GLOBALISASI INFORMASI DAN PERUBAHAN POLITIK DAN ADMINISTRASI PEMERINTAHAN INDONESIA PASCA ORDE BARU - Ulber Silalahi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2012)
The globalization of information in the early 21st century has made the country, government, and the world community closer and connected quickly. The world has become borderless, so what's happening in the world's first and second world will soon be known to the third world. Moreover, the globalization of information makes a success of democratization and decentralization in the country and desentralisasion encourage democratization in other countries,including Indonesia. This study aims to explain the impact of globalization on the political administration of government information post-New Order Indonesia. The method used is descriptive, qualitative study of literature. The findingssuggest that the globalization of information have changed the political administration post-New Order Indonesia become more democratic and decentralized. Visible indication of democratization democratization elections (presidential and legislative elections as well as representatives) and local elections (local elections and local legilslatif members) andgovernance based on good governance, while decentralization seems indicative of an increase of area and district and city up to 69.6 with the details of the province increased 26.9, the district increased 76.8, the city government increased 60.3%. This increase will impact on the improvement of government management, public service management and welfare of citizens